1999
DOI: 10.1038/sj.onc.1202810
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin driven v-Ha-ras induces multilineage pulmonary epithelial hyperplasias and neoplasms

Abstract: We initiated a transgenic model for primary pulmonary neuroendocrine cell (PNEC) hyperplasia/neoplasia using v-Ha-ras driven by the neural/neuroendocrine (NE)-speci®c calcitonin promoter (rascal). Previously, we showed that nitrosamine treated rodents develop PNEC hyperplasia but non-NE lung tumors, with variable outcomes presumably re¯ecting ras activation in multiple cell lineages. Interestingly, all rascal transgenic mouse lineages develop hyperplasias of NE and non-NE cells but mostly non-NE lung carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 60 publications
1
16
0
1
Order By: Relevance
“…However, many if not most tumours are composed of multiple histological types (Thurlbeck and Churg, 1995;Fraire et al, 1987). Such variation in a presumably clonal lesion has led to the suggestion that lung cancers arise from a multipotential stem cell component of the normal tissue, a hypothesis supported by the analysis of model systems (Sunday et al, 1999). It is very likely that transcript profiling will lead to further subdivisions within these overall classes of disease, some which mirror preexisting pathological classes and some which are novel (Garber et al, 2001;Bhattacharjee et al, 2001).…”
Section: Introductionmentioning
confidence: 84%
“…However, many if not most tumours are composed of multiple histological types (Thurlbeck and Churg, 1995;Fraire et al, 1987). Such variation in a presumably clonal lesion has led to the suggestion that lung cancers arise from a multipotential stem cell component of the normal tissue, a hypothesis supported by the analysis of model systems (Sunday et al, 1999). It is very likely that transcript profiling will lead to further subdivisions within these overall classes of disease, some which mirror preexisting pathological classes and some which are novel (Garber et al, 2001;Bhattacharjee et al, 2001).…”
Section: Introductionmentioning
confidence: 84%
“…Thus they concluded that lung tumorigenesis can progress through other genetic pathways not requiring activation of the K-ras oncogene. A more recent study that used transgenic models showed a role of v-Has-ras in the induction of multilineage pulmonary epithelial hyperplasia and neoplasia (85).…”
Section: Molecular Studiesmentioning
confidence: 99%
“…On the other hand, it appears that PNECs may renew themselves but do not contribute to epithelial cells in experimental models that cause Clara cell injury (10). Although PNECs are very rare in normal adult lungs, hyperplasias emerge during many human inflammatory processes, as well as in animal models (11)(12)(13)(14)(15). For instance, PNECs may be involved, directly or indirectly, in the pathogenesis of cystic fibrosis (16) and diffuse idiopathic pulmonary neuroendocrine cell hyperplasia in adults (17)(18)(19), and in neuroendocrine cell hyperplasia of infancy (20).…”
mentioning
confidence: 99%